Integration of Artificial Intelligence in Modern Communication Systems - Khodijah, Siti; Hasanuddin, Muhammad; Rizki, Cindy Atika (Raskha Media Group, 2024)
The integration of Artificial Intelligence (AI) in modern communication systems marks a transformative era in the way data is transmitted, processed, and interpreted. This study explores the role of AI technologies—including machine learning, deep learning, and natural language processing—in enhancing the performance, efficiency, and security of communication networks. By examining various AI-driven applications such as intelligent routing, automated network management, and real-time speech and image recognition, this research highlights the significant improvements in latency reduction, bandwidth optimization, and system adaptability. Furthermore, the paper discusses challenges in AI implementation, including data privacy, computational complexity, and ethical concerns. The findings emphasize that while AI presents vast opportunities for innovation in communication systems, a robust framework is necessary to ensure reliability, transparency, and sustainable development.